Using Horticulturalists' Input to Inform a Home Horticultural Website Redesign Process - Jason D. Ellis; B. Lynn Gordon; Lana Johnson (Journal of Applied Communications, 2012)
The Internet is a growing source of information for consumers. Website design and development become important factors in website usability as consumers’ Internet access increases and they seek home horticulture and gardening resources. The University of Nebraska–Lincoln developed a website in the 1990s to supplement its Backyard Farmer television program. Consumers’ expectations of websites changed as technology changed, which resulted in the site no longer meeting visitors’ needs. Two focus groups evaluating the website’s usefulness as an information source were conducted with home and professional horticulturalists. Participants were most interested in locating concise information about horticulture and gardening on a website that was easy to navigate; had many links to additional information; and contained timely and current information. Overall, content quality, usability and aesthetics were highly ranked as important for a “perfect” website.
Keywords: Website testing; Horticulture; Gardening; Usability; Design; Focus Groups; Television